RESPONSIBILITY OF HUMANITARIAN VALUES AND JUSTICE OF THE EXECUTION APPLICANT, REGARDING THE SAFETY OF THE EXECUTION RESPONDENT’S PROPERTY: CASE STUDY: RULING No. 109/Pdt/2016/PT.Pbr - Bintang Arbakmis; Tamrin; Abd Thalib (International Conference On Law And Social Sciences, 2024)
The Execution System is the embodiment of regulations regarding a form of coercive action in the implementation of court decisions, the implementation of decisions of quasi-judicial institutions, and certain legal documents. With the issuance of decision Number 109/PDT/G/2016/PT.PBR, execution is not just a system but is a hope, guarantee, and means to fulfill justice for execution applicants. Execution is a solution to ensure the safety of the property belonging to the applicant for execution. The main problems in this research are: 1) what is the responsibility of the execution applicant's human values and justice towards the safety of the execution applicant's property: Case study of decision No. 109/Pdt/2016/PT.Pbr, at the Dumai District Court; 2) what are the obstacles to the respondent's execution of decision case no. 109/Pdt/2016/PT.Pbr, at the Dumai District Court. The research method used is normative juridical with analytical descriptive research specifications. From the results of this research, execution system regarding the responsibility of the execution applicant's human values and justice, towards the safety of property belonging to the execution applicant: Case study of decision no. 109/Pdt/2016/PT.Pbr, at the Dumai District Court, legal protection must be given in accordance with the Directorate General of General Justice 2019 concerning execution guidelines in district courts regarding the stages of execution and Article 196 HIR / 207 RBg, but after a material review regarding this Law, its regulation and implementation is in accordance with Constitutional Court Decision No. 18/PUU-XVII/2019 and Indonesian National Police Regulation No. 8 of 2011 concerning Securing the Execution of Collateral. As for the obstacles to the respondent's execution in decision case no. 109/ Pdt/2016/PT.Pbr, at the Dumai District Court, these are, among other things, Internal Factors: 1) not all execution teams are able to carry out voluntarily and without guarantees of safety 2) not all execution teams have a good social and religious spirit in carrying out execution. External Factors: 1) the party being executed is difficult to find, 2) there is no good faith on the part of the person being executed.